4D-BIM to enhance construction waste reuse and recycle planning: Case studies on concrete and drywall waste streams. (October 2020) - Guerra, Beatriz C.; Leite, Fernanda; Faust, Kasey M.
Highlights: 4D-BIM applied to construction waste reuse and recycle planning. Discretizing construction waste generation into quantities for reuse and recycle. Visual identification and planning of on-site concrete waste reuse opportunities. Two case studies demonstrated and validated with ground truth data and literature. Abstract: Despite pressing attention on construction waste management (CWM) issues, low rates of construction waste (CW) reuse and recycling (R&R) remain a limitation in construction projects. In recent years, Building Information Modeling (BIM) has gained momentum for CWM purposes; its data-richness, visualization, and simulation capabilities provide an opportunity to enhance CW R&R planning at the project level. In this context, this study proposes temporal-based algorithms integrated with 4D-BIM for the planning of concrete and drywall waste R&R throughout construction projects. Two case studies from Central Texas were used for the demonstration of the algorithms, and estimates were validated with ground truth data and literature values from different projects in North America. The overarching objective of the proposed algorithms is to streamline estimation and visual planning of CW for on-site reuse, and off-site recycling – therefore promoting a more proactive and schedule-based CWM plan. In addition, the approach improves team communication around CWM goals of the project. Moreover, through the use of 4D-BIM, on-site waste reuse opportunities are planned in advance, thus, improving resource recovery and minimizing waste disposal in landfills.